Antifungal potential of multi-drug-resistant Pseudomonas aeruginosa: harnessing pyocyanin for candida growth inhibition - Oves, Mohammad; Khan, Mohd Shahnawaz; Al-Shaeri, Majed; Khan, Mohammad Saghir (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Pseudomonas aeruginosa is notorious for its multidrug resistance and its involvement in hospital-acquired infections. In this study, 20 bacterial strains isolated from soil samples near the Hindan River in Ghaziabad, India, were investigated for their biochemical and morphological characteristics, with a focus on identifying strains with exceptional drug resistance and pyocyanin production. Methods The isolated bacterial strains were subjected to biochemical and morphological analyses to characterize their properties, with a particular emphasis on exopolysaccharide production. Strain GZB16/CEES1, exhibiting remarkable drug resistance and pyocyanin production. Biochemical and molecular analyses, including sequencing of its 16S rRNA gene (accession number LN735036.1), plasmid-curing assays, and estimation of plasmid size, were conducted to elucidate its drug resistance mechanisms and further pyocynin based target the Candida albicans Strain GZB16/CEES1 demonstrated 100% resistance to various antibiotics used in the investigation, with plasmid-curing assays, suggesting plasmid-based resistance gene transmission. The plasmid in GZB16/CEES1 was estimated to be approximately 24 kb in size. The study focused on P. aeruginosa’s pyocyanin production, revealing its association with anticandidal activity. The minimum inhibitory concentration (MIC) of the bacterial extract against Candida albicans was 50 μg/ml, with a slightly lower pyocyanin-based MIC of 38.5 μg/ml. Scanning electron microscopy illustrated direct interactions between P. aeruginosa strains and Candida albicans cells, leading to the destruction of the latter. Discussion These findings underscore the potential of P. aeruginosa in understanding microbial interactions and developing strategies to combat fungal infections. The study highlights the importance of investigating bacterial-fungal interactions and the role of pyocyanin in antimicrobial activity. Further research in this area could lead to the development of novel therapeutic approaches for combating multidrug-resistant infections.